Novel mutations of CRB1 in Chinese families presenting with retinal dystrophies - Yang, Liping (Molecular Vision, 2014)
PURPOSE: To identify disease-causing mutations in Chinese families who presented with retinitis pigmentosa (RP) and Leber congenital amaurosis (LCA). METHODS: The pathogenic variant in a Chinese family with autosomal dominant RP was investigated with a specific hereditary eye disease enrichment panel (HEDEP) based on targeted exome capture technology. The identified variant was confirmed with Sanger sequencing. CRB1 mutations in 67 patients with sporadic retinal dystrophy were examined with Sanger sequencing. RESULTS: Compound heterozygous mutations were identified in a family who had undergone HEDEP analysis. After complete sequence analysis of the CRB1 gene was performed in 67 patients with sporadic retinal dystrophy, other compound heterozygous mutations were detected in three families. The mutations included three novel heterozygous mutations: c.3059delT (p.M1020SfsX1), c.3460T>A (p.C1154S), and c.4207G>C (p.E1403Q). The mutation frequency of CRB1 in this study was 5.9% (8/136). CONCLUSIONS: Our findings broaden the spectrum of CRB1 mutations and the phenotypic spectrum of the disease in Chinese patients. The results from this study show that patients with LCA carry CRB1 null mutations more frequently than patients with RP.